Ensino de emaranhamento quântico no Ensino Médio utilizando a sociointeracionista de Vigotsky: uma sequência didática partindo do clássico para o quântico - Santos, Klinsmann Patrick dos (2023)
In this work, a proposal for a didactic sequence (DS) is presented to approachquantumentanglement (EQ) in High School (EM), as well as the results of a pedagogical interventioncarried out with 3rd grade students of a public school unit. from the city of Madre deDeus-BA, located in the metropolitan region of Salvador, aiming to introduce the EQtheme, aswellas concepts related to the theme. The DS was elaborated from Vygotsky's sociointeractionistperspective. Methodologically, the proposal consists of the use of semiotic mediators (videos,simulators, images and texts) and social mediation (interaction between the subjects involvedin the teaching and learning processes). massive presence of digital informationandcommunication technologies (TDIC) in the school routine, which enhance the access anduseof these semiotic mediators in different moments and situations, allowing students tohavesocial mediations outside the classroom. Thus, SD activities were developed withaviewtosurveying the students' spontaneous conceptions regarding MC and QMconcepts. Afterthepresentation of each video, students were encouraged to debate, mediated by the teacher. Theuse of videos as semiotic mediators proved to enhance debates between peers, sincetheevaluation was carried out through the answers to the guiding questions andproblemsituations using a virtual entanglement simulator (IVMZ) and short videos. The dataweretranscribed and analyzed, looking for evidence of internalization of the EQconcept. It isworth mentioning that the research participants had a greater maturity in the responsesandanalyzes of the IVMZ during the DS, although they did not present the masteryofentanglement, with that there was a construction, (re)signification of the physical concept ofMQ. A conclusion that seems plausible to us is the fact that the use of semiotic andsocialmediators, associated with classical concepts such as wave and particle, allowed theresearchparticipants to act in the zone of proximal development so that they could appropriatetheideaof quantum entanglement.